Dlg, Scrib and Lgl regulate neuroblast cell size and mitotic spindle asymmetry. - Albertson, R.; Doe, C.Q. (Nature Cell Biology, 2003)
Asymmetric cell division is important in generating cell diversity from bacteria to mammals. Drosophila melanogaster neuroblasts are a useful model system for investigating asymmetric cell division because they establish distinct apical-basal cortical domains, have an asymmetric mitotic spindle aligned along the apical-basal axis, and divide unequally to produce a large apical neuroblast and a small basal daughter cell (GMC). Here we show that Discs large (Dlg), Scribble (Scrib) and Lethal giant larvae (Lgl) tumour suppressor proteins regulate multiple aspects of neuroblast asymmetric cell division. Dlg/Scrib/Lgl proteins show apical cortical enrichment at prophase/metaphase, and then have a uniform cortical distribution. Mutants have defects in basal protein targeting, a reduced apical cortical domain and reduced apical spindle size. Defects in apical cell and spindle pole size result in symmetric or inverted neuroblast cell divisions. Inverted divisions correlate with the appearance of abnormally small neuroblasts and large GMCs, showing that neuroblast/GMC identity is more tightly linked to cortical determinants than cell size. We conclude that Dlg/Scrib/Lgl are important in regulating cortical polarity, cell size asymmetry and mitotic spindle asymmetry in Drosophila neuroblasts.